Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Terasi Udang Di Desa Rantau Panjang - Niken Rahmadyah; Irwan Irwan; Mira Nur Aisah; M. Reza Shah Fahlevi Lubis; Khairul Faiz Batubara; Diana Diana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Marketing strategy is a form of plan on how to design the direction of the target market towards consumer demand in determining the company's expectations to attract customers' interest in the products offered in increasing sales. The problem faced by the Shrimp Shrimp business in Rantau Panjang Village is the absence of a brand and a small business while the management of production in rural areas is difficult to penetrate the market share, for that it is necessary to do a strategy in this Shrimp Shrimp business. The purpose of this study was to determine the right marketing strategy for shrimp paste. The data collection method was obtained from Observation, Interview and Documentation using the Quantitative Descriptive Method, the data that had been obtained was then analyzed using the SWOT analysis method, by looking at Strengths, Weaknesses, Opportunities, Threats. The results show that based on the research above, it can be concluded that the problem that occurs in the shrimp paste business is the difficulty in marketing production as a result of the absence of trademark rights and a very simple marketing system.